PENGARUH GANGGUAN LINGKUNGAN ANTARIKSA PADA SISTEM ELEKTRONIK LAPAN-TUBSAT (EFFECT OF SPACE ENVIRONMENT DISTURBANCE IN LAPAN-TUBSAT SATELLITE) - Najati, Nayla (Indonesian Journal of Aerospace, 2012)
LAPAN-TUBSAT has been operated more than five years. During the operation, LAPAN-TUBSAT faces several anomaly. It could be observed by using real time telemetry and long time telemetry. When and where an anomaly appeared can be detected with long time telemetry. Anomaly event on LAPAN-TUBSAT’s PCDH is caused by Single Event Latch-Up (SEL) that happen in scale of weeks.These conditions required LAPAN-TUBSAT operators to take action in order to make LAPAN-TUBSAT back to normal operation. This paper describes statistic of SEL that occur in LAPAN-TUBSAT. Almost 70% of SEL event take place at South Atlantic Anomaly (SAA) and the rest at polar.